The Influence Capital Structure, Liquidity, Dividend policy, and Profitability to Firm Value - Sriyanto, Edi; Hikmah, Khoirul; Sukarno, Agus (Universitas Mercu Buana, 2025)
This study aims to examine the effect of capital structure, liquidity, dividend policy, and profitability on firm value. The research employs a quantitative approach using secondary data obtained from the financial statements of companies listed on the LQ45 Index of the Indonesia Stock Exchange. A purposive sampling technique was applied, resulting in 70 firm-year observations from 2020 to 2024. The data were analyzed using multiple linear regression with SPSS 20. The findings reveal that capital structure, liquidity, dividend policy, and profitability jointly have a significant impact on firm value. However, capital structure individually shows no significant effect. In contrast, liquidity, dividend policy, and profitability each demonstrate a positive and significant influence on firm value. These results suggest that firms can enhance their value by improving financial performance, particularly through maintaining adequate liquidity, implementing consistent dividend policies, and increasing profitability.